The CD4 (T4) antigen is an essential component of the receptor for the AIDS retrovirus. - Dalgleish, A; Beverley, P; Clapham, P; Crawford, D; Greaves, M; Weiss, R (1984)
Acquired immune deficiency syndrome (AIDS) is characterized by opportunistic infections and by 'opportunistic neoplasms' (for example, Kaposi's sarcoma). Persistent generalized lymphadenopathy (PGL) is epidemiologically associated with AIDS, especially in male homosexuals. A subset of T lymphocytes positive for the CD4 antigen (also termed T4 antigen), is depleted in AIDS and PGL patients. A retrovirus found in T-cell cultures from these patients is strongly implicated in the aetiology of AIDS because of the high frequency of isolation and the prevalence of specific antibodies in the patients. Here we have detected cell-surface receptors for the AIDS retrovirus (human T-cell leukaemia virus-III (HTLV-III) and lymphadenopathy-associated virus-1 (LAV-1) isolates) by testing the susceptibility of cells to infection with pseudotypes of vesicular stomatitis virus bearing retroviral envelope antigens, and by the formation of multinucleated syncytia on mixing virus-producing cells with receptor-bearing cells. Receptors were present only on cells expressing CD4 antigen; among 155 monoclonal antibodies tested, each of the 14 anti-CD4 antibodies inhibited formation of syncytia and blocked pseudotypes. Productive infection of CD4+ cells with HTLV-III or LAV-1 markedly reduced cell-surface expression of CD4. In contrast, receptors for HTLV-I and HTLV-II were not restricted to CD4+ cells, were not blocked by anti-CD4 antibodies; cells productively infected with HTLV-I and HTLV-II expressed surface CD4. Hence, we conclude that the CD4 antigen is an essential and specific component of the receptor for the causative agent of AIDS.